THE IMPACT OF SMARTPHONES ON PSYCHOLOGICAL STABILITY - Akramova Gulrukh Alihanovna (Bright Mind Publishing, 2026)
This article examines the impact of smartphone usage on adolescents’ psychological stability. Modern teenagers spend a significant amount of time using smartphones, tablets, and other digital devices, which can lead to stress, anxiety, decreased attention span, and emotional instability. The study analyzes both international research and empirical data on adolescents’ digital habits, highlighting the risks of excessive screen time.
Keywords: Smartphones, adolescents, psychological stability, digital addiction, stress, anxiety, screen time, digital literacy, mental health.